Cultural Heritage Evaluation Based on Analytic Hierarchy Process and Fuzzy Control: Case Study of the South Manchuria Railway in China - Wenqi Qiao; Siyi Pang; Mengjin Guo (Buildings)
The South Manchuria Railway, being the earliest constructed railway in Northeast China, has preserved a vast array of modern architectural heritage along its route, which holds significant research value. This study takes the urban agglomerations along the Shenyang–Yingkou section of the South Manchuria Railway as the research object, convening scholars from various fields to construct a hierarchy analysis model for heritage value and using fuzzy control tools to mitigate the impact of subjective cognition on the experimental results, thereby determining the weight values of the influencing factors of modern architectural heritage along the South Manchuria Railway. We invited professional scholars and stakeholders to score the modern architectural heritage, and after combining the weight values derived from the hierarchy analysis model and calculating the weighted average, the heritage value scores were determined for each piece of modern architectural heritage. This study utilizes heritage value scores to measure the degree of danger and the extent of protection required for these architectural heritages, identifies the current shortcomings and insufficiencies in the protection and renewal of these heritages, and compares the effectiveness of heritage conservation efforts in various cities and towns.